2022
DOI: 10.3390/plants11141827
|View full text |Cite
|
Sign up to set email alerts
|

Studies Regarding the Pharmaceutical Potential of Derivative Products from Plantain

Abstract: In this study, three types of extracts isolated from leaves of Plantain (Plantago lanceolata) were tested for their chemical content and biological activities. The three bioproducts are combinations of polysaccharides and polyphenols (flavonoids and iridoidic compounds), and they were tested for antioxidant, antifungal, antitumor, and prebiotic activity (particularly for polysaccharides fraction). Briefly, the iridoid-enriched fraction has revealed a pro-oxidant activity, while the flavonoid-enriched fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…31 Based on extensive research, it has been shown that the pharmacological advantages and impacts attributed to P. major are inherently connected to beta-sitosterol. 32,33 The bioactive ingredient not only contributes to the medical capabilities of the plant but also plays a crucial part in characterizing them; therefore, gaining knowledge about the extraction process, features, and advantages of Plantago major may provide significant insights into the medicinal potential of this plant. In this study the identification of the derived molecule was achieved by the integrated use of Fourier Transform Infrared Spectroscopy and Nuclear Magnetic Resonance analytical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…31 Based on extensive research, it has been shown that the pharmacological advantages and impacts attributed to P. major are inherently connected to beta-sitosterol. 32,33 The bioactive ingredient not only contributes to the medical capabilities of the plant but also plays a crucial part in characterizing them; therefore, gaining knowledge about the extraction process, features, and advantages of Plantago major may provide significant insights into the medicinal potential of this plant. In this study the identification of the derived molecule was achieved by the integrated use of Fourier Transform Infrared Spectroscopy and Nuclear Magnetic Resonance analytical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the antimicrobial activity was carried out by comparison with the antibiotic specific to each microorganism tested (Babeanu et al, 2022;Zaharie et al, 2022;Radu et al, 2010;Ioan et al, 2020). The evaluation of the antimicrobial activity was carried out on the basis of an empirical scale, established as follows: 6.1≤inhibition diameter≤15 mm=local antimicrobial activity; 15<inhibition diameter≤20 mm=moderate antimicrobial activity; inhibition diameter >20 mm = significant antimicrobial activity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, an antioxidant effect was highlighted, both in vitro and in vivo, in certain metabolites exposed to specific exopolysaccharides of Bifidobacterium animalis strains, which succeeded in inhibiting oxide and superoxide radicals [ 21 , 22 , 23 ]. The gut microbiome allows complex nutrients, such as the cell wall components in plants [ 24 , 25 , 26 , 27 ] or cereals (cellulose, pectin, hemicellulose, lignin, mucins, and polysaccharides (prebiotics)), to be transformed into simple sugars that are fermented to form short-chain fatty acids (SCFAs). These compounds (SCFAs) contain organic compounds such as acetate, propionate, and butyrate and are usually amplified by the activity of the bioactive compounds that exist in fractions isolated from plants [ 28 , 29 ] or cereals, such as polyphenolic compounds [ 30 , 31 , 32 ], which are easily highlighted with Folin–Ciocalteu reagent [ 29 ].…”
Section: Introductionmentioning
confidence: 99%